Предмет: Математика,
автор: doiiia111
Lim x->0 1-cos8x / 3x^2
Lim x-> бесконечность ( x-1 x) ^2-3x
Limx->бесконечность (2x+3 5x+7)^x+1
Ответы
Автор ответа:
0
x→0 ; cosx→ 1 - x²/2 ⇒
lim x→0 (1- cos8x)/3x² = lim (1-1+(8x)²/3x² = lim (64x²/2)/3x² =
= 32/3 = 10' 2/3
lim n→∞ (1+1/n)^n = e
lim x→∞ (1 - 1/x)^(2-3x) ={ lim (1-1/y)^2] / {[lim (1-1/x)^x]³ =
= 1/(1/e)³ = e3
lim x→∞ [(2+3/x)/(5+7/x)]^(x+1) = 2/5
lim x→0 (1- cos8x)/3x² = lim (1-1+(8x)²/3x² = lim (64x²/2)/3x² =
= 32/3 = 10' 2/3
lim n→∞ (1+1/n)^n = e
lim x→∞ (1 - 1/x)^(2-3x) ={ lim (1-1/y)^2] / {[lim (1-1/x)^x]³ =
= 1/(1/e)³ = e3
lim x→∞ [(2+3/x)/(5+7/x)]^(x+1) = 2/5
Похожие вопросы
Предмет: Русский язык,
автор: stas87002
Предмет: Русский язык,
автор: natasamilyh
Предмет: Химия,
автор: Аноним
Предмет: Литература,
автор: Крисс2005
Предмет: Биология,
автор: MissSamaPoSebe